Leveraging your host systems with web services transforming legacy applications into SOA-based composite applications. - Ketabchi, Farshid (SOA webservices journal.)
The promise of service-oriented architecture (SOA), increasing benefits of Web services, and continued business use of legacy systems have all coalesced to usher in a new era of flexible IT alignment for business needs. With only a fraction of legacy application being Web-enabled and increasing enterprise investment in SOA, organizations need to know how they can use Web services to leverage their legacy systems.